Mantle dynamics and characteristics of the Azores plateau - Adam, C. (2018)
Situated in the middle of the Atlantic Ocean, the Azores plateau is a region of elevated topography encompassing the triple junction between the Eurasian, Nubian and North American plates. The plateau is crossed by the Mid-Atlantic Ridge, and the Terceira Rift is generally thought of as its northern boundary. The origin of the plateau and of the Terceira Rift is still under debate. This region is associated with active volcanism. Geophysical data describe complex tectonic and seismic patterns. The mantle under this region is characterized by anomalously slow seismic velocities. However, this mantle structure has not yet been used to quantitatively assess the influence of the mantle dynamics on the surface tectonics. In this study, we use a highly resolved tomography model to model the convection occurring in the mantle beneath the Azores region. The convection pattern points out two distinct upwelling, thus proving that the volcanism emplacement is created by a buoyant mantle upwelling. The modeled dynamic topography recovers well the characteristics of the depth anomaly associated with the Azores plateau, except for the south-eastern most part, thus proving that most of the depth anomaly associated with the Azores plateau is created by the present-day mantle dynamics. The stresses induced by the mantle convection can account for the lifting regime observed over the Azores plateau and the Terceira Rift, and its consequences in terms of surface morphology and seismicity. (C) 2012 Elsevier B.V. All rights reserved.